Self-Strengthement Movement and 100 Days Reforms through Classical Elites Theory - Mgeladze, Shota (WILAYAH: The International Journal of East Asian Studies, 2025)
The paper used the comparative case study model to test the assumptions of classical elite theory. Analyzing the Chinese reformation attempt during the Qing dynasty revealed the limited scope of actions of the leaders. The existence of national elites limits their political environment. However, leaders’ motivations and strategies can vary by choosing different factions. Analyzing such relations is the key to understanding why reformation was carried out or not successfully. Theoretical test of classical elites’ assumptions revealed that they can explain how elites keep the power, but further elaboration is needed whether reforms can succed or fail.